Eco-friendly Traps to Control Sexapa sp. - Meldy L.A. Hosang (International Coconut Community, 2010)
The indigenous insect, Sexava sp. causes serious damage to coconut palms/plantations in some provinces of Indonesia. The objective of this study is to develop and evaluate the performance of three types of eco-friendly Balitka MLA-traps, standing alone and in combination with insect glue (fly glue and tangle foot). Balitka MLA trap was designed to capture the Sexava spp. especially during the night when they move from one place to another through the coconut trunk. The traps made from black cloth, insect glue, metal wire, and yarn were fixed on the coconut trunks at 1 – 1.5 M height. Three different types of traps namely Balitka MLA Trap A, B, and C were developed and evaluated. The study found that trap type C captured nymphs and adult of 1 – 7 nymphs/palm/day or 30-210 nymphs/palm/month. The trap also enabled natural enemies such as spiders and lizards to catch the snared pests easily. A total of 106 to 131 nymphs were caught by tangle foot and insect glue respectively after 3 months of fixing the traps in the field. These traps could potentially be used together with a biological control method to replace the use of insecticides in Sexava-infested areas. This study was conducted in Talaud District, North Sulawesi Province, Indonesia from 2006 to 2007. Based on the study results, and considering the simplicity and eco-friendliness of the trap type C, it is recommended that it be used in coconut plantations to bring down the population of this insect pest, Sexava sp. and thereby control its damage to coconut palms.